Premenstrual Syndrome among Health Care Providers - Shabana Kanwal, Farah Hassan Khan, Nighat Ali Shah, Nusrat Shah (Pakistan Journal of Medical & Health Sciences, 2023)
An observational cross-sectional study carried out in Koohi Goth Hospital from 25-07-2019 to 25-01-2020. Objective of Study: The objective of study was to access the frequency of premenstrual syndrome among health care providers (Doctors and paramedical staff) and to list the major clinical features of premenstrual syndrome among those health care providers. Methodology: Out of 200 health care providers reported having PMS 100 (50%) were Doctors and 100 (50%) were paramedical staff who were interviewed and studied in further details using a pre-designated semi structured Data Collection Questionnaire which included socio dermographic and clinical profile of the responders. In socio dermographic profile age, marital status, designation (doctors and paramedical staff) were asked while clinical profile includes those signs and symptoms of respondent that has occurred in at least 2 or 3 periods of their last menstrual cycles and resolved completely by the end of leaving a symptom free week. Results: A total of 200 subjects meeting the inclusion criteria were included in the study. The lowest age of subjects was 20 years and the highest age was 40 years. The highest number of health care providers 125(62.5%) belonged to age class 20-24 years, 60(30%) were in age category of 25-30 years and 15(7.5%) were in age group of 31-40 years. There were 100(50%) doctors and 100(50%) were paramedics. Out of 200 health care providers 75(37.5%) were married and 125(62.5%) were un-married. Out of 200 study participants premenstrual syndrome (PMS) was found in 152(76%) subjects and 48(24%) were without the syndrome. Out of 125 (62.5%) study subjects who were in the age category of 20-24 years PMS was found in 110(80%). Out of 60(30%) subjects of age category of 25-30 years PMS was found in 35(58.3%) and out of 15 (7.5%) subjects of age category of 31-40 years PMS was found 7(46.6%). Out of 152(76%) of subjects with PMS, loss of appetite was found in 40(26.3%), strong desire for food found in 10(6.5%), subject felt thirsty, were 24(15.7%), excessive sleep was found in 25(16.4%), loss of sleep was found in 15(9.8%), increased sexual desire was found in 3(1.9%). Decrease sexual desire was found in 4(2.6%). Loss of confidence was found in 18(11.8%) and social Isolation was in 50(32.8%). Out of 152 subjects symptoms of swelling was found in 20(13.1%). Breast swelling was found in 29(19.1%). Nausea was experienced by 15(9.8%). Weight was gained by 9(5.9%) subjects. Headache was experienced by 30(19.7%) subjects. Fatigue was found in 80(52.6%) subjects and constipation was found in 21(13.8%). Conclusion: Premenstrual syndrome is a condition that affects adolescent more frequently. The diagnosis of PMS is miscalculated since diverse criterias were used in published studies. This study was shows that PMS is a common problem among women of reproductive use group. Marital status and age do not affects the prevalence of PMS. Fatigue, social isolation loss of appetite, feel thirsty, loss of confidence and excessive sleep were most common psychological symptoms, while headache, breast swelling and constipation were most common physical symptoms. Largely ignored both clinically and scientifically in Pakistan, PMS merits further biosocial investigations and doctors should pay attention and adopt comprehensive measure in order to reduce the recurrence and improve the quality of life.